Uncertain Future Dwelling: Emergent Interiors of the Metaverse - Dunstan, Belinda J.; Stonham, Michael; Dincer, Demet (UI Scholars Hub, 2024)
Contemporarily, a flood of digital interior architectural imagery has emerged of spaces developed for the Metaverse, a forthcoming immersive 3D virtual world. These spaces are not bound by the conventions of architectural practice nor the demands of the physical world, providing an opportunity for design exploration and innovation in the future of interiors and positing challenges to core architectural concepts that have accompanied traditional practice. This research offers a visual analysis of aesthetic trends and new typologies present in the interior architectural spaces designed for the Metaverse. The analysis features a curated and collaged collection of works from ten creators of Metaverse spaces, categorised to examine the impact of digital architectural spaces that increasingly detach from the needs of physical dwellings. The research reveals commanding visual trends in Metaverse interior imagery that challenge traditional notions of interiority and dwelling and finds aesthetic signifiers of belonging in spaces that Augé (1995/2009) would neatly classified as an empirical 'non-place.' Positioned as a form of heterotopia in a realm where architecture is being designed for the purely visual, we posit that the less recognisable these spaces become, the more potential they hold for innovation in both the Metaverse and in dialogue with real-world interior architecture.